The Cambridge economic history of modern Britain. Volume I, 1700-1870 - Floud, Roderick; Humphries, Jane; Johnson, Paul (Cambridge University Press, 2014)
A new edition of the leading textbook on the economic history of Britain since industrialization. Combining the expertise of more than thirty leading historians and economists, Volume 1 tracks Britain's economic history in the period ranging from 1700 to 1870 from industrialisation to global trade and empire. Each chapter provides a clear guide to the major controversies in the field and students are shown how to connect historical evidence with economic theory and apply quantitative methods. New approaches are proposed to classic issues such as the causes and consequences of industrialisation, the role of institutions and the state, and the transition from an organic to an inorganic economy, as well as introducing new issues such as globalisation, convergence and divergence, the role of science, technology and invention, and the growth of consumerism. Throughout the volume, British experience is set within an international context and its performance benchmarked against its global competitors.